Impact of happiness at work and organizational culture on employee performance: Job satisfaction as mediation - Winda, Hyasinta; Hasanudin, Hasanudin; Shalahuddin, Ahmad (Institute of Computer Science (IOCS), 2025)
This study examines the relationship between happiness at work and organizational culture of employee performance at the Pontianak City Regional Finance and Assets Agency (BKAD), with job satisfaction as a mediating variable. The quantitative technique used in this study was a census (saturated sample). surveyed everyone who worked at BKAD (Pontianak City Regional Finance and Assets Agency) in West Kalimantan. Data were analyzed using structural equation modeling (SEM) with SMART PLS 4.0 statistical software after 53 people were surveyed using a questionnaire. There is a statistically significant relationship between happiness at work and job satisfaction and performance, according to the findings of this study. Performance was not affected by organizational culture, but job satisfaction was. Furthermore, research has shown that happiness at work has a significant impact on employee performance. The significance of job satisfaction in improving employee performance is demonstrated by the fact that it mediates the relationship between happiness at work, organizational culture and performance.